Risk factors for lateral pelvic lymph node metastasis in patients with lower rectal cancer: a systematic review and meta-analysis - Zeng, De-xing; Yang, Zhou; Tan, Ling; Ran, Meng-ni; Liu, Zi-lin; Xiao, Jiang-wei (Frontiers in Oncology, 2023)
Background and Objective: Lateral pelvic lymph node (LPLN) metastasis is one of the prominent reasons for local recurrence (LR) in patients with rectal cancer (RC). The evaluation criteria of lateral lymph node dissection (LLND) for patients in eastern (mainly in Japan) and western countries have been controversial. The aim of this study was to analyse the risk factors for LPLN metastasis in order to guide surgical methods.We searched relevant databases (Embase (Ovid), Medline (Ovid), PubMed, Cochrane Library, and Web of Science) for articles published between 1 January 2000 and 05 October 2022 to evaluate the risk factors for LPLN metastasis in patients with RC in this meta-analysis.Results: A total of 24 articles with 5843 patients were included in this study. The overall results showed that female sex, age <60 years, pretherapeutic CEA level >5 ng/ml, clinical T4 stage (cT4), clinical M1 stage (cM1), distance of the tumour from the anal verge (AV) <50 mm, tumour centre located below the peritoneal reflection (Rb), short axis (SA) of LPLN ≥8 mm before nCRT, short axis (SA) of LPLN ≥5 mm after nCRT, border irregularity of LPLN, tumour size ≥50 mm, pathological T3-4 stage (pT3-4), pathological N2 stage (pN2), mesorectal lymph node metastasis (MLNM), lymphatic invasion (LI), venous invasion (VI), CRM (+) and poor differentiation were significant risk factors for LPLN metastasis (P <0.05).This study summarized almost all potential risk factors of LPLN metastasis and expected to provide effective treatment strategies for patients with LRC. According to the risk factors of lateral lymph node metastasis, we can adopt different comprehensive treatment strategies. High-risk patients can perform lateral lymph node dissection to effectively reduce local recurrence; In low-risk patients, we can avoid overtreatment, reduce complications and trauma caused by lateral lymph node dissection, and maximize patient survival and quality of life.